DCT and Wiener filter based on approach for speech enhancement using a single microphone - OU Shi-feng; ZHAO Xiao-hui; GU Hai-jun (Tongxin xuebao)
Considering the enhancement of speech corrupted by complicated additive noise,a novel algorithm was proposed based on discrete cosine transform（DCT） and Wiener filter using a single microphone.This algorithm did not rely on any speech signal model and could efficiently attain the optimal estimation of clean speech components using successive noisy speech components and minimum mean square error estimation in DCT domain.Furthermore,it could overcome the disad-vantage of independent assumptions in classic methods for speech components.Simulation results demonstrate that the pro-posed algorithm possesses good performance both in objective and subjective tests with different kinds of noise.